On the structure of linked 3-folds - Biancofiore, Aldo; Fania, Maria Lucia (Revista Matemática Complutense, 2001)
The structure of 3-folds in P6 which are generally linked via a complete intersection (f1, f2, f3) to 3 folds in P6 of degree d ≤ 5 is determined. We also give three new examples of smooth 3-folds in P6 of degree 11 and genus 9. These examples are obtained via liaison. The first two are 3-folds linked via a complete intersection (2, 3, 3) to 3-folds in P6 of degree 7: (i) the hyperquadric fibration over P1 and (ii) the scroll over P2. The third example is Pfaffian linked to a 3-dimensional quadric in P6.